Comercialização do tomate de mesa no estado de São Paulo : análise de transmissão de preços - Silva Neto, Waldemiro Alcântara da (2007)
The central objective of this work was the study of the chain of marketing of tomato of table in nature in the state of São Paulo. To study the behavior of the margins of marketing of the involved agents, to measure and to verify the implications of the seasonality in the prices of the producer, wholesaler and retailer. To verify as if gives the transmission of prices among these agents and if it is asymmetric or not. The understood period was of January of 1995 to the March of 2006. They are had as hypotheses: producer is affected by the seasonality and pertinent risks to agriculture has minor to be able of negotiation and therefore lesser income and the transmission of prices among the agents is asymmetric. First, the behavior of the series of prices was verified and the edge of marketing in the period, later aspect of the seasonality in the three levels of prices was measured and analyzed. Through econometrical tests and application of model VAR, it was verified aspects of the transmission of prices and identified strong evidence of asymmetry. The model used for the Asymmetry in the Transmission of Prices was the applied one for Griffith and Piggott (1994), with adaptations the peculiarities of the product studied in this work. As main results: the retailer is the agent with greater to be able of negotiation, the producer is affected by the seasonality and has better incomes and the model of transmission of prices is asymmetric.